Landscaping multilingualism in the urban community of Limassol: policies, practices and visions - Nicolaou, Anna; Parmaxi, Antigoni; Papadima-Sophocleous, Salomi; Boglou, Dimitrios (My University, 2016)
Contemporary era is characterized by unprecedented movement of goods, capitals, people and ideas. Living and working in such an era, everyday communication activities are challenged by the struggle to understand different cultural groups who share different viewpoints and perceptions. In such a context, many policy makers and university researchers call attention to the need to understand how intercultural communication occurs. With this in mind, this study builds up a picture of how communication occurs in various aspects of life in an under-researched city, Limassol, Cyprus with regard to multilingualism and plurilingualism. More specifically, it explores issues pertaining to multilingualism and plurilingualism in education, the public sphere, economic life, the private sphere, and urban spaces. Drawing from both the primary and secondary data collected during the two phases of the research, the study examines certain aspects of multilingualism, such as good practice in language learning for immigrants, the role of linguistic support in social inclusion, provision for communication and cultural exchange with neighbouring languages, promotion of intercultural dialogue, and the changing face of migration in the Limassol civic context. The study also addresses more specific research questions such as language visibility and invisibility, affordances at the level of governance or policy, as well as challenges and obstacles involved in creating and managing multilingualism in the city of Limassol. Findings demonstrate policies and practices implemented in the various aspects of city life in order to promote intercultural dialogue and mutual understanding. As a result of the findings, suggestions for best practices, introduction or improvement of policies and visions of the multilingual cities are put forward.
Keywords: Language diversity; Social inclusion; Multilingualism; Language visibility; Language policy; Linguistic landscapes